Lectio praecursoria: The Cowboy Politics of an Enlightened Future: History, Expansionism, and Guardianship in Isaac Asimov’s Science Fiction - Jari Käkelä (Fafnir, 2016)
Jari Käkelä (PhD) defended his dissertation The Cowboy Politics of an Enlightened Future: History, Expansionism, and Guardianship in Isaac Asimov’s Science Fiction at the University of Helsinki, Finland on the 9th of September, 2016. This essay is a slightly edited version of the lectio praecursoria given by Käkelä before the defense. Käkelä’s dissertation can be read at the e-thesis service: https://helda.helsinki.fi/handle/10138/166004